Kindheit und Jugend eines ungarischen Aristokraten im Lichte der Memoiren Paul Esterházys - Duchoňová, Diana (Theatrum historiae, 2012)
This paper deals with Palatine Paul Esterhazy’s diary written as an adult’s reflection of the child- hood and youth. Paul Esterhazy belonged among the most prominent figures of Hungary in the early Modern Age period as he managed to draw on the successful policies pursued by his father, Nikolaus Esterhazy. He too was awarded the rank of the Palatine, the supreme regional administration, and held the office for 32 years. The author of this study focuses on his childhood on his father’s farmstead and his studies in Trnava described in vivid detail in his memoires. As a consequence of the demise of his two elder siblings, he was forced to yield to the interests of the family’s policies and to refrain from his spiritual career. He had to marry his niece Ursula Esterhazy, the heir of the Thurzos’ property. In his memoires Paul also reminisces about another reason for the change of his position in the family’s hierarchy, namely the battle with the Turks near Vozokany, where four young family members died. Paul Esterhazy’s reminiscences of his childhood and youth can be interpreted as an effort to support the memory of the family and dynasty and to accent his predestination to become the head of the Esterhazy dynasty.